Akhenaten : a woman, a eunuch, a victim of pathology or a religious representation? - Marston, J. E. (Journal for semitics, 2010)
The images of Akhenaten continue to incite debate largely because those from the Amarna period represent an extraordinary break from traditional royal portrayals. Contrary to established conventions, Akhenaten is depicted with an elongated skull, a prominent jaw, heavy lips and eyelids, a thin neck, slender waist, a distended stomach, large thighs and thin lower legs. Numerous theories have been advanced to explain this apparent schism, many of which are premised upon the images as portraits of the king. Early theories suggested Akhenaten was a woman, a eunuch or the result of generations of incestuous royal marriages. Later theorists proffered medical pathologies such as lipodystrophy, hydrocephaly, hyperpituitarism, eunuchoidism, Klinefelter's Syndrome, Froehlich's Syndrome, and most recently Marfan's Syndrome. The preferred view is that these images were not intended to be interpreted as portraits, but rather as artistic devices to reflect the new religious status of the king and queen, who were objects of worship in their own right.